Collaborative care for depression yields similar improvement among older and younger rural adults. Issue 1 (18th September 2021) - Renn, Brenna N.; Johnson, Morgan; Powers, Diane M.; Vredevoogd, Mindy; Unützer, Jürgen
Abstract: Background: Depressive disorders are among the most prevalent mental health conditions; however, significant barriers to treatment access persist. This study examined differences in depression outcomes between younger and older adults in a large‐scale implementation demonstration of the collaborative care model (CoCM). Methods: Secondary data analysis of a longitudinal, observational implementation demonstration at eight primary care clinics across low‐resourced rural or frontier areas of the Western United States. Seven of these clinics were federally qualified health centers. The sample consisted of 3722 younger (18–64 years) and older (65+ years) adult primary care patients diagnosed with unipolar depression. All participants received depression treatment via CoCM, which enhances usual primary care and makes efficient use of specialists by using a behavioral healthcare manager and a psychiatric consultant to support primary care providers. Clinics were followed for up to 27 months. Patients were followed until they completed treatment or dropped out. The Patient Health Questionnaire (PHQ‐9) assessed depressive symptoms at baseline (enrollment) and at most follow‐up contacts. The primary treatment outcome was a change between a patient's first and last recorded PHQ‐9 scores. Results: Across both age groups, there was an average overall reduction of 6.9 points on the PHQ‐9. Older adults demonstrated a greater decrease in depression scores of 2.06 points (95% CI −2.98 to −1.14, p < 0.001) on the PHQ‐9 compared with younger adults. Estimates were robust when adjusting for gender, race, and clinic. Conclusions: CoCM resulted in meaningful improvement in depressive symptoms across age groups. Abstract : See related editorial by Kazan and Gebara in this issue.